2019
DOI: 10.1155/2019/1602892
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus membranaceus and Panax notoginseng, the Novel Renoprotective Compound, Synergistically Protect against Podocyte Injury in Streptozotocin-Induced Diabetic Rats

Abstract: This study was aimed at investigating the synergistical protective effects of Astragalus membranaceus (AG) and Panax notoginseng (NG) on podocyte injury in diabetic rats. Diabetes was induced in rats by a single intraperitoneal injection of streptozotocin at 55 mg/kg. Diabetic rats were then orally administrated with losartan, AG, NG, and AG plus NG (2 : 1) for 12 weeks. Albuminuria, biochemical markers, renal histopathology, and podocyte number per glomerulus were measured. Podocyte apoptosis was determined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 46 publications
0
28
0
Order By: Relevance
“…If the injury continues or the dose of the damaging agent increases, cytoplasmic TUNEL can be converted to a “messy” picture of dispersed TUNEL ( Figure 3 G) attributed to late stages of cell destruction due to necrosis and spillage of cellular cytoplasm and debris. For example, both cytoplasmic and dispersed TUNEL was observed in cisplatin-treated mice [ 71 , 72 ] and rats [ 144 ], and in podocyte injury in streptozotocin-induced diabetic rats [ 145 ]. Dispersed necrotic TUNEL was also observed during uranyl acetate-induced nephrotoxicity in mice [ 101 ].…”
Section: Tunel Patterns As a Source Of Additional Informationmentioning
confidence: 99%
“…If the injury continues or the dose of the damaging agent increases, cytoplasmic TUNEL can be converted to a “messy” picture of dispersed TUNEL ( Figure 3 G) attributed to late stages of cell destruction due to necrosis and spillage of cellular cytoplasm and debris. For example, both cytoplasmic and dispersed TUNEL was observed in cisplatin-treated mice [ 71 , 72 ] and rats [ 144 ], and in podocyte injury in streptozotocin-induced diabetic rats [ 145 ]. Dispersed necrotic TUNEL was also observed during uranyl acetate-induced nephrotoxicity in mice [ 101 ].…”
Section: Tunel Patterns As a Source Of Additional Informationmentioning
confidence: 99%
“…Moreover, some of the components in SQ have been scientifically proven to possess anti-apoptosis or autophagy-regulating properties. Previous researches have reported that Astragalus membranaceus plus Panax notoginseng can synergistically ameliorate renal injury in diabetic nephropathy partly through inhibiting apoptosis ( Zhai et al., 2019 ) or promoting autophagy ( Wen et al., 2020 ). Calycosin, one of the major components in Astragalus membranaceus, has been verified to inhibit oxidative stress-induced cardiomyocyte apoptosis via activating estrogen receptor-α/β ( Liu B. et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we have identified that the major compositions of SQ include ginsenosides, notoginsenoside R1, calycosin, and so on (Tian et al, 2019;Xu et al, 2019). Among these compositions, ginsenoside Rg 1, notoginsenoside R1 and calycosin are capable of reducing apoptosis (Chen et al, 2001;Liu B. et al, 2016;Huang et al, 2017;Tong et al, 2019;Zhai et al, 2019), notoginsenoside R1 and calycosin also exhibit effects on activating autophagy in HT29 cells, podocytes or renal mesangial cells (Huang et al, 2017;Wen et al, 2020). Yet, their roles on renal I/R injury and tubular cells have never been elucidated and deserves to be addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Previously, we found that HUANG QI combined with SAN QI reduces urinary protein excretion, decreases renal pathological changes, and improves apoptosis and shedding of kidney podocytes in DKD rats [33]. NIU BANG ZI extract reduces podocyte damage and proteinuria symptoms of DKD mice by enhancing PP2A activity in podocytes and protects kidney function [34].NIU BANG ZI extract also signi cantly reduces blood sugar in DKD mice and reduces the damage to the kidney [35].…”
Section: Introductionmentioning
confidence: 94%